Bride Kidnapping and Labour Supply Behaviour of Married Kyrgyz Women - Reza Arabsheibani; Alma Kudebayeva; Altay Mussurov (Institute of Labor Economics (IZA), 2021)
Using data from the 2011 and 2016 Life in Kyrgyzstan surveys, we examine Kyrgyz women's labour supply elasticities at the extensive margin. We use Heckman's two-step approach to predict earnings for the non-participating women and then use these predictions to estimate the participation equation. We find that women's labour supply decision is not influenced by their earnings. We also show that there exists a significant gap in employment propensities among ethnic Kyrgyz women in consensual or arranged marriages compared to women in kidnapped-based marriages. This finding suggests that the practice of bride abduction adversely affects women's probability of employment and might have negative consequences on their economic well-being.
Keywords: J01; J16; J22; 330; labour supply; women; bride kidnapping; Kyrgyzstan